2022
DOI: 10.48550/arxiv.2209.07852
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simultaneous measurement of muon neutrino $ν_μ$ charged-current single $π^+$ production in CH, C, H$_2$O, Fe, and Pb targets in MINERvA

A. Bercellie,
K. A. Kroma-Wiley,
S. Akhter
et al.

Abstract: Neutrino-induced charged-current single π + production in the ∆(1232) resonance region is of considerable interest to accelerator-based neutrino oscillation experiments. In this work, high statistics differential cross sections are reported for the semi-exclusive reaction νµA → µ − π + + nucleon(s) on scintillator, carbon, water, iron, and lead targets recorded by MINERvA using a wide-band νµ beam with Eν ≈ 6 GeV. Suppression of the cross section at low Q 2 and enhancement of low Tπ are observed in both light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…MINERvA recently measured charged-current charged-pion production on different nuclei [9]. Using the same neutrino beam as used here, MINERvA found that the ratio of pions produced on Fe or Pb compared to scintillator is lower than predicted by current models.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…MINERvA recently measured charged-current charged-pion production on different nuclei [9]. Using the same neutrino beam as used here, MINERvA found that the ratio of pions produced on Fe or Pb compared to scintillator is lower than predicted by current models.…”
mentioning
confidence: 81%
“…The background levels from non-quasielastic-like interactions are 36% in the scintillator and are 33 − 45% in the nuclear targets, with the lowest background in the Pb targets. The fact that the physics backgrounds are lower in Pb than in the lighter nuclei stems from the fact that pion production is suppressed in heavier nuclei relative to C, as measured by MINERvA [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MINERvA: Results and Prospects Deborah A. Harris is seeing a larger ratio for iron and lead to CH than the current models predict. This may be due in part to mis-modeling of pion absorption: MINERvA has also measured pion production in its nuclear targets [19], and sees a relative suppression of the ratio of pion production cross sections for iron or lead divided by scintillator compared to the simulation. If fewer pions are produced than predicted by the simulation, then there are two possibilities for how this might manifest in the quasielastic-like sample.…”
Section: Pos(now2022)032mentioning
confidence: 99%
“…As expected, the former is consistent with unity. 2 The CH cross sections used to calculate the ratios, were reweighted to use a flux that matched the flux used to calculate the C, Fe or Pb cross sections [18].…”
mentioning
confidence: 99%